Gangliosides combined with mild hypothermia provides neuroprotection in a rat model of traumatic brain injury. Issue 13 (19th July 2021) - Li, Zhaolin; Zhang, Hongwei; Cao, Cangzhu; Qian, Tao; Li, Hong
Abstract : Traumatic brain injury (TBI) remains a major cause of disability and death in modern society. In this study, we explored the neuroprotection role of the combination of gangliosides (GM) and mild hypothermia (MH) and the potential effect on oxidative stress injuries in a rat model of TBI. All 50 rats were randomized to five groups: (1) NC group: undergoing surgery without hit; (2) TBI group: undergoing surgery with hit; (3) GM group: TBI treated with gangliosides; (4) MHT group: TBI treated with MH; (5) GM+MHT group: TBI treated with gangliosides and MH. Spatial learning impairments, neurological function injury, Evans Blue leakage, brain MRI and oxidative stress injuries were assessed. The protein levels of Cleaved-caspase 3 and CytC were also detected. Both GM and MHT could rescue TBI-induced spatial learning impairments, improve neurological function injury and brain edema. In addition, the combination of them has a better therapeutic effect. Through the MRI, we found that compared with the TBI group, the brain tissue edema area of GM group, MHT group, and GM+MHT group was smaller, the occupancy effect was weakened, and the midline was slightly shifted. Compared with the GM group and MHT group, these changes in the GM+MHT group were much smaller. GM combined with MH-alleviated TBI-induced oxidative stress injuries and apoptosis. Our study reveals that GM and MH potentially provide neuroprotection via the suppression of oxidative stress injuries and apoptosis after TBI in rats.